PERAN KOMUNIKASI INTERNAL DAN GAYA KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN SEMANGAT KERJA PERANGKAT DESA DI DESA SUKAJADI - Nanang Juhandi Hermawan; Farida Sartika; Deden Hidayatulloh (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2026)
This study aims to analyze the influence of internal communication and the village head's leadership style on the work morale of village apparatus in Sukajadi Village, Cianjur Regency. The primary background of this research is the phenomenon of low discipline and delays in task completion, which indicate a decline in the work morale of village officials. This research employs a quantitative approach using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) via SmartPLS 4.0 software. The entire population of 30 village apparatus members was used as the research sample through a saturated sampling (census) technique. Hypothesis testing results indicate that internal communication has a positive and significant effect on work morale, with a path coefficient of 0.667 and a t-statistic of 4.698. Leadership style was also found to have a positive and significant effect on work morale, with a coefficient of 0.322 and a t-statistic of 2.245. An R-Square value of 0.974 shows that both variables simultaneously contribute 97.4% to the work morale of the village apparatus. These findings confirm that internal communication is the most dominant factor in shaping work motivation within Sukajadi Village. In conclusion, enhancing the work morale of village officials can be optimally achieved through strengthening transparent communication systems and developing more participatory leadership capacities for the village head.